Contrasting roles of small metallic elements M (M = Cu, Zn, Ni) in enhancing the thermoelectric performance of n-type PbM0.01Se. Issue 11 (6th March 2020) - Qian, Xin; Wang, Dongyang; Zhang, Yang; Wu, Haijun; Pennycook, Stephen J.; Zheng, Lei; Poudeu, Pierre F. P.; Zhao, Li-Dong
Abstract : The carrier concentration of PbCu0.01 Se sample increases suddenly, which results from the release of 3d orbital electrons in Cu + ions. Abstract : The metallic elements with a small atomic radius can not only compensate for the intrinsic vacancies to improve the carrier mobility, but also can form interstitials to reduce lattice thermal conductivity. In this work, we investigate the contrasting roles of three different metallic elements with small atomic radius on the thermoelectric properties of n-type PbM0.01 Se (M = Cu, Zn, Ni). We find that all the metallic elements can increase the carrier concentration as electron donors and improve the electrical transport properties. In addition, the lattice thermal conductivity of PbSe can be significantly decreased through the formation of interstitials by the incorporated extra metallic elements. We also find that the PbCu0.01 Se sample exhibits a unique and complex behavior compared with the other samples due to the diffusion and the thermally activated oxidation of Cu + ions. When the temperature increased to 673 K, the carrier concentration of PbCu0.01 Se sample increases suddenly and continues to increase by nearly two folds, which we ascribe to the release of 3d orbital electrons in Cu + ions. This results in a strong decoupling of the charge and heat transport in the material, which can be manifested by the overestimation of the electronic thermal conductivity when assuming strong electron–phonon coupling in Wiedemann–Franz law. A maximum ZT of ∼1.6 can be reached at 773 K and the average ZT of ∼0.96 can be achieved in PbCu0.01 Se. Our results demonstrate the exceptional contrasting behavior of Cu in PbSe by comparing with Zn and Ni, and the thermoelectric performance of n-type PbSe can be enhanced through the introduction of extra metallic elements with small radius.